Convergence : a Foreigner novel - Cherryh, C. J. (Cherryh, C. J. Foreigner universe., 2017)
Alpha Station, orbiting the world of the atevi, has taken aboard five thousand human refugees from a destroyed station in a distant sector of space. With supplies and housing stretched to the breaking point, it is clear that the refugees must be relocated down to the planet, and soon. But not to the atevi mainland: rather to the territory reserved for human, the island of Mospheira. Tabini-aiji, the powerful political head of the atevi, tasks his brilliant human diplomat, Bren Cameron, to negotiate with the Mospheiran government. For the Alpha Station refugees represent a political faction that the people of Mospheira broke from two centuries ago, and these Mospheirans are not enthusiastic about welcoming these immigrants from space. In the decades Bren has served Tabini, he has become enmeshed in the atevi world in a way no human ever has before. Bren is now an atevi lord, with his own estate on the mainland, his own household, and his own Assassin<U+2019>s Guild bodyguards. He is a treasured resource to Tabini and has become close to Tabini<U+2019>s young son and heir, Cajieri, the first atevi child ever to grow up in the presence of a human.